Chemical Purification, Analysis and Screening core facility: overcoming challenges of natural product research in drug discoveryTT - - Calcul, Laurent (Université des Antilles (2015-....), 2019)
The CPAS offers instrumentation and expertise in fractionation, purification, and various chemical analyses to support research groups for drug discovery of synthetic and natural products. An example of three important studies will be presented at the conference to illustrate the basic services of CPAS.